3D Reconstruction and Prediction of Sialolith Surgery - Jamyson Oliveira Santos; Brunna da Silva Firmino; Matheus Santos Carvalho; Jean de Pinho Mendes; Lucas Novaes Teixeira; Sérgio Lúcio Pereira de Castro Lopes; André Luiz Ferreira Costa; Antonione Santos Bezerra Pinto (Case Reports in Dentistry)
Imaging examinations play an important role in the diagnosis of sialolithiasis, whose symptoms are initially confounded with other diseases. The objective of the present case report is to highlight imaging and processing techniques as well as image analysis for the preoperative assessment and planning of surgical interventions and adequate treatment of massive sialoliths. A 35-year-old male patient presented complaining of pain in the submandibular region and purulent secretions from a lingual caruncle with slightly increased volume in the region. Imaging examinations were ordered as follows: cone beam computed tomography, ultrasonography, and three-dimensional reconstruction, including clinical evaluation. A final diagnosis of sialolithiasis was established. Surgery was indicated and carried out by using a lateral transcervical approach for complete resection of the gland, which was based on the calculation of the total volume of the sialolith, thus increasing the surgery’s success.